Smaller businesses and e-innovation: a winning combination in Australia. Issue 2 (20th May 2019) - Alam, Khorshed; Adeyinka, Adewuyi Ayodele; Wiesner, Retha
Abstract : Purpose: The purpose of this paper is to understand whether or not factors that impact the performance–innovation nexus differ from one percentage level of performance to another among small- and medium-sized enterprises in regional Australia, with a specific focus on e-innovation by strategic and non-strategic firms in the agricultural sector and in other industries. Design/methodology/approach: Researchers implicitly assumed that the performance–innovation relationship is uniform across high-level, mid-level and low-level performing small- and medium-sized enterprises. In this study, the authors analysed performance at different percentage levels. Findings: The findings indicate that the levels of small- and medium-sized enterprises performance have a significant difference in terms of the factors influencing their performance. The industry may be a determinant of performance, which is similar in the case of the topmost performers in the non-agricultural sector. The major findings of this study are as follows: the performance–innovation relationship differs by the percentage level of small- and medium-sized enterprises performance; and Solow's productivity paradox exists at the firm level. Practical implications: The authors recommend that rural policies should target low-performing firms. Moreover, researchers should adopt methodologies that shed light on the differences in the performance–innovation nexus across performance levels rather than one-size-fits-all methodologies that are often adopted. Originality/value: The major contributions of this study are that the performance–innovation relationship differs by the level of small- and medium-sized enterprises performance, and Solow's productivity paradox exists at the firm level.